Effects of chlorhexidine preprocedural rinse on bacteremia in periodontal patients: a randomized clinical trial (Journal of Applied Oral Science, 2017)
Objective: Single dose of systemic antibiotics and short-term use of mouthwashes reduce bacteremia. However, the effects of a single dose of preprocedural rinse are still controversial. This study evaluated, in periodontally diseased patients, the effects of a pre-procedural mouth rinse on induced bacteremia. Material and Methods: Systemically healthy individuals with gingivitis (n=27) or periodontitis (n = 27) were randomly allocated through a sealed envelope system to: 0.12% chlorhexidine pre-procedural rinse (13 gingivitis and 13 periodontitis patients) or no rinse before dental scaling (14 gingivitis and 15 periodontitis patients). Periodontal probing depth, clinical attachment level, plaque, and gingival indices were measured and subgingival samples were collected. Blood samples were collected before dental scaling, 2 and 6 minutes after scaling. Total bacterial load and levels of P. gingivalis were determined in oral and blood samples by real-time polymerase chain reaction, while aerobic and anaerobic counts were determined by culture in blood samples. The primary outcome was the antimicrobial effect of the pre-procedural rinse. Data was compared by Mann-Whitney and Signal tests (p